European Society for Vascular Surgery (ESVS) 2025 Clinical Practice Guidelines on the Management of Diseases of the Mesenteric and Renal Arteries and Veins - Koelemay, Mark J.; Geelkerken, Robert H.; Kärkkäinen, Jussi; Leone, Nicola; Antoniou, George A.; de Bruin, Jorg L.; Gombert, Alexander; Gottsätter, Anders; Iborra, Elena; Ronchey, Sonia; Spanos, Konstantinos; van den Berg, Jos C.; et al. (Elsevier BV, 2026)
Objective: The European Society for Vascular Surgery (ESVS) has developed clinical practice guidelines for the care of patients with diseases of the mesenteric and renal arteries and veins, in succession to the first 2017 guidelines, with the aim of assisting physicians and patients in selecting the best management strategy.
Methods: These guidelines are based on scientific evidence and expert opinion. By summarising and evaluating the best available evidence, recommendations for the diagnosis and treatment of patients have been formulated. The recommendations are graded according to the new ESVS clinical practice guidelines class of recommendation grading system, where the strength (class) of each recommendation is graded from I to III, and the letter A to C marks the level of evidence.
Results: A total of 102 recommendations have been issued on the management of chronic arterial mesenteric ischaemia, median arcuate ligament syndrome, acute arterial mesenteric ischaemia, non-occlusive mesenteric ischaemia, venous mesenteric thrombosis and ischaemia, occlusive disease of the renal arteries and veins, visceral artery aneurysms, and spontaneous isolated dissection of the visceral arteries.
Conclusion: These 2025 ESVS clinical practice guidelines provide comprehensive and up to date advice to physicians and patients on the management of diseases of the mesenteric and renal arteries and veins.